The Origins and Development of the Definite Article in Egyptian-Coptic - Maxim Kupreyev (Ksiegarnia Akademicka Publishing, 2014)
The first appearance of the emphatic demonstratives pA/tA/nA in northern Egyptian letters of the 6th Dynasty and their absence from southern Egyptian sources indicates the growing difference between the language variants spoken in these broadly defined regions. Originating from the Old Egyptian pronominal stems p-/t-/n-, the use of these new demonstratives expands rapidly during the Middle Kingdom. In their weak form as definite articles, they indicate that a noun is knownin discourse and thus signal a hitherto hidden grammatical category – definiteness. Once the definite article is grammaticalised and starts to be used with a priori definite nouns such as pA nTr wa ‘the sole god’ or pA HqA ‘the ruler’ (18th Dynasty), the indefinite article appears. The further development in Demotic and Coptic shows that the article was on the way to becoming a noun marker. When attached to a relative phrase, it created a new noun, which could be further determined (xenpetnanouf ‘some good deeds’, ppetouaab ‘the saint’). The following article traces the regional origins of the definite article as well as the main principles governing their development.